mRNA cancer vaccines from bench to bedside: a new era in cancer immunotherapy - Alireza Shariati; Pouria Khani; Farzad Nasri; Hamed Afkhami; Arya Khezrpour; Sina Kamrani; Fatemeh Shariati; Sajad Alavimanesh; Mohammad Hossein Modarressi (Biomarker Research)
Abstract Harnessing the power of the immune system to target cancer cells is one of the most appealing approaches for cancer therapy. Among these immunotherapies, messenger ribonucleic acid (mRNA) cancer vaccines are worthy of consideration, as they have demonstrated promising results in clinical trials. These vaccines have proven to be safe and well-tolerated. They can be easily mass-produced in a relatively short time and induce a systemic immune response effective against both the primary tumor and metastases. Transcripts encoding immunomodulatory molecules can also be incorporated into the mRNA, enhancing its efficacy. On the other hand, there are some challenges associated with their application, including mRNA instability, insufficient uptake by immune cells, and intrinsic immunogenicity, which can block mRNA translation. Many innovations have been suggested to overcome these obstacles, including structural modification (such as 5’ cap modification), optimizing delivery vehicles (especially dendritic cells (DCs) and nanoparticles), and using antigens that can enhance immunogenicity by circumventing tolerance mechanisms. A popular approach is to combine mRNA cancer vaccines with traditional and novel cancer treatments like chemotherapy, radiotherapy, and immune checkpoint blockade (ICB). They are most efficacious when combined with other therapies like ICBs. There is still a long way to go before these vaccines enter the standard of care for cancer patients, but with the incredible pace of development in this field, their clinical application will soon be witnessed. This review highlights the recent advances and challenges of mRNA cancer vaccines. Finally, some of the most prominent clinical applications of these vaccines will be reviewed.